The potential mechanism of Aidi injection against neuroblastoma—an investigation based on network pharmacology analysis - Dai, Shuyang; Gu, Yaoyao; Zhan, Yong; Zhang, Jie; Xie, Lulu; Li, Yi; Lu, Yifei; Yang, Ran; Zhou, Enqing; Chen, Deqian; Liu, Songbin; Zheng, Shan; et al. (Frontiers in Pharmacology, 2024)
Background: Aidi injection, a classic Traditional Chinese medicine formula, has been on a broader scale in treating a variety of cancer. In this study, we aimed to explore the potential anti-tumor effects Aidi injection in the treatment of neuroblastoma (NB) using network pharmacology.To uncover the anti-NB mechanism of Aidi injection, a network pharmacology-based approach, and molecular docking validation were employed. The compounds and target genes were collected from the Traditional Chinese Medicine System Pharmacology (TCMSP) database and Bioinformatics Analysis Tool for Molecular mechANism of Traditional Chinese Medicine (Batman-TCM) database. The protein interaction network was constructed through the STRING database. The clusterProfiler (R package) was utilized to annotate the bioinformatics of hub target genes. The gene survival analysis was performed on R2, a web-based genomics analysis application.The iGEMDOCK was applied for molecular docking validation and Gromacs were adopted to validate molecular docking results. Furthermore, we investigated the anticancer effects of Gomisin B and Ginsenoside Rh2 on human neuroblastoma cells using a cell viability assay. The western-blot assay were used to validate the protein levels of target genes in Gomisin B and Ginsenoside Rh2 treated neuroblastoma cells.Results: A total of 2 critical compounds with 16 hub target genes were identified for treating NB. All 16 hub genes could potentially influence the survival of NB patients. The Top 3 genes (EGFR, ESR1, and MAPK1) were considered the central hub genes from the drugs-compounds-hub target genes-pathways network. The Endocrine resistance and estrogen signaling pathways were identified as 4 the theruputic pathways through the Kyoto Encyclopedia of Genes and Genomes(KEGG) analysis. The Gominsin B and Ginsenoside Rh2 had a good binding ability to the target protein in molecular docking.The results of cell experiments showed that anti-neuroblastoma effect of the Gominsin B and Ginsenoside Rh2. In addition, the administration of Gominsin B over-regulated the expression of ESR1 protein in MYCN amplified neuroblastoma cells.In the present study, we investigated the potential pharmacological mechanisms of Aidi on NB, found the anti-neuroblastoma effect of Gominsin B on neuroblastoma, providing the clinical proof of Aidi in treating NB, and made references for further research.